2022
DOI: 10.3389/fgene.2022.831866
|View full text |Cite
|
Sign up to set email alerts
|

A Final Frontier in Environment-Genome Interactions? Integrated, Multi-Omic Approaches to Predictions of Non-Communicable Disease Risk

Abstract: Epidemiological and associative research from humans and animals identifies correlations between the environment and health impacts. The environment—health inter-relationship is effected through an individual’s underlying genetic variation and mediated by mechanisms that include the changes to gene regulation that are associated with the diversity of phenotypes we exhibit. However, the causal relationships have yet to be established, in part because the associations are reduced to individual interactions and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 153 publications
(170 reference statements)
0
5
0
Order By: Relevance
“…CNCDs are characterised by the fact that they can be a burden on a person's health for a number of years or decades, or in some cases throughout life. The idea that it is not possible to provide compelling evidence of the transmissibility of a CNCD from one person to another [183] can no longer be supported in view of recent epigenetic insight [184,185]. Epigenetic changes in this context are defined as reactions to external stimuli that lead to pathological dysfunctions and long-term changes in gene expression.…”
Section: Medical Significancementioning
confidence: 99%
See 1 more Smart Citation
“…CNCDs are characterised by the fact that they can be a burden on a person's health for a number of years or decades, or in some cases throughout life. The idea that it is not possible to provide compelling evidence of the transmissibility of a CNCD from one person to another [183] can no longer be supported in view of recent epigenetic insight [184,185]. Epigenetic changes in this context are defined as reactions to external stimuli that lead to pathological dysfunctions and long-term changes in gene expression.…”
Section: Medical Significancementioning
confidence: 99%
“…This has changed and we now have a different understanding of the prevention and treatment of oral diseases [189], due, on the one hand, to new molecular insights into the oral microbiome [190] and a change in how we view the oral biofilm [191] and, on the other, to the fact that confirmed links have been observed between systemic and dental CNCDs [189,192]. These observations have led to various new hypotheses concerning the aetiology and prevention of these diseases, which is why the WHO and the FDI now consider oral health to be a key indicator of overall health [183][184][185][186][187][188][189][190][191][192][193][194][195].…”
Section: Medical Significancementioning
confidence: 99%
“…Research on genome regulatory impacts of environmental exposures and their relationship with the risk of NCDs could present some desirable health impacts. Development of polygenic risk scores (PRS) for NCDs, and assigning phenotypic impacts to BPA can help predict an individual's genetic propensity with the BPA exposure risks associated with NCDs traits [81]. Hüls et al [82] demonstrated associations between high PRS for obesity and sociodemographic and lifestyle factors in obese children.…”
Section: Epigenetic Studiesmentioning
confidence: 99%
“…Nonetheless, the interactions between the environment and our genetic make‐up and how these interactions might ultimately influence disease risk are only starting to be elucidated. [ 34 ]…”
Section: Introductionmentioning
confidence: 99%